One Health policy communities’ perspectives on zoonoses risk factors and management: A multiple qualitative methods approach - Lisset M. Dumet; Erin Kenzie; Julia Goodman; Veronika Merino Osorio; Vanessa Cruz Chavez; Ruth Atto; Percy Vilchez Barreto; Seth O’Neal (CABI One Health, 2025)
Abstract Zoonoses emergence and endemicity are serious global public health problems that disproportionately affect low-resource settings. One Health (OH) serves as a framework to understand the interconnection of zoonoses risk factors and incentivizes collaboration, coordination, and communication among sectors. However, OH encounters barriers related to power imbalances, gaps in coordination, and conflicts of interest among diverse communities of practice, which are groups that share a problem and domain of interest and engage in collective learning. This research aims to elucidate the mental models of policy communities, which are representations of the environment, and how humans explain and predict their surroundings to describe their perspectives on zoonoses’ risk factors and management. We used a multiple methods approach, including qualitative system dynamics and rapid qualitative methods (RQM), to describe the perspectives of policy communities regarding the drivers of zoonoses emergence and endemicity and the complexity of zoonoses management. Participants included national and sub-national policy makers and key informants integral to zoonoses programs in Peru, including representatives of human, animal, and environmental systems. We completed 77 semi-structured interviews from June 2023 to November 2023, and the final analytical sample included 75 interviews, excluding 2 incomplete interviews. Participants’ mental models were represented with synthesized systems dynamics diagrams. Main themes and quotes from the RQM added context to the diagrams and described participants’ perspectives regarding zoonoses management complexity. Representatives from animal, human, and environmental public organizations described a similar structural conceptualization of the risk factors related to pets, humans, wildlife, and livestock, identifying economic, social, and environmental risk factors linked to zoonoses emergence and endemicity. Central themes include: global structural economic and social forces; factors affecting biodiversity and natural reservoirs; environmental changes; medical and public health services; country economic factors; rural reliance on farming and limited funding; agricultural factors; and water, hygiene, and sanitation-responsive governance. The system dynamics diagrams illustrated interrelationships between pet, human, wildlife, and livestock populations. However, risk factors related to zoonoses affecting livestock were more prominently represented. Participants recognized the need to apply OH to address zoonoses; however, contextual factors, such as regional adaptation, were necessary in poor rural areas. The study’s results inform about value systems that guide political action and decision making among the diverse OH communities of practice. A similar application in high-income settings could identify differences in zoonoses’ risk factors that may not be related to rural vulnerability or poverty. Further research is needed to describe the interconnection of organizational factors associated with OH collaborations. One Health impact statement Zoonoses control and prevention require collaboration, communication, and coordination among disciplines, organizations, communities, and regions. In this context, policy communities with different perspectives and agendas require a shared understanding of the problem to align their interests for collaboration. One Health provides an adequate framework for context-specific analysis of the policy process, incentivizing the inclusion of various levels of government and sectors. Our study investigated policy communities’ perspectives on the drivers and consequences of zoonoses’ emergence and endemicity in a low-resource setting. We included policy makers and experts from national and sub-national Peruvian organizations in animal, environmental, and human systems. This study examines the existing policy process and narratives surrounding the prevention and control of zoonoses in Peru. It is the first step to understanding how systems could be efficient and effective in facilitating multisectoral collaboration and coordination while informing efforts to scale up One Health programs in low-resource settings.